The Russian Revolution - Pascal, Michel ([s.l] : Audiovisual Enterprises Ltd., 1994)
On November 7th 1917 the Bolsheviks stormed the Winter Palace in Petrograd (soon to become Leningrad) the Soviet State came into existence under the leadership of Vladimer Lenin and Leon Trosky. The video contains original newsreelfootage covering the major events of over 4 years of conflict and the events that changed world history
Copy available in DVD format
Title from data sheet
Keywords: Soviet Union -- History -- Revolution, 1917 -- 1921 -- Motion picture and the revolution